Stability of Flavan-3-ols, Theaflavins, and Methylxanthines in 30 Industrial Green, Black, and White Tea (Camellia sinensis L.) Extracts Characterized via Liquid Chromatography Techniques - Antonio M. Inarejos-Garcia; Julia Heil; Sonia Guilera Bermell; Gertrud E. Morlock (MDPI AG, 2023)
Commercially available tea extracts for dietary supplements and nutraceuticals are standardized to characteristic components of Camellia sinensis L., such as epigallocatechin gallate (EGCG) and total catechins or polyphenols. However, since most commercial tea extracts are highly concentrated into only one molecule such as EGCG, the comparatively less stable catechin, the oxidative stability of the extract during the 24-month shelf life was questioned. It was hypothesized that the overall oxidative stability is reduced for highly purified/concentrated tea extracts due to the absence of other natural antioxidants stabilizing the complex mixture. Via liquid chromatographic analysis, the individual chromatographic profiles of 30 commercial white, green, and black tea extracts were evaluated and compared regarding oxidative stability and functional properties. The contents of bioactive flavan-3-ols, theaflavins, and methylxanthines differed much from what was claimed by the suppliers. At the end of the product shelf life, most of the commercial green and black tea extracts showed a decrease in the flavan-3-ol content, the main bioactive components of tea. A high EGCG content to the detriment of other possibly stabilizing flavan-3-ols or antioxidants in tea was found to explain the lower oxidative stability of such tea extract products. A natural overall composition of molecular structures was found to be superior to a strong enrichment in just one molecule.